2005
DOI: 10.1002/pon.924
|View full text |Cite
|
Sign up to set email alerts
|

The Mini-Mental Adjustment to Cancer (Mini-MAC) scale: construct validation with a Greek sample of breast cancer patients

Abstract: This investigation is a Greek validation of the Mini-Mental Adjustment to Cancer (Mini-MAC) scale, an instrument derived from the MAC and designed to measure styles of coping with cancer. A sample of 225 women diagnosed with breast cancer completed this questionnaire. Statistical analyses using structural equation modeling (SEM) confirmed Watson's original five first-order factors underlying Mini-MAC items: Helplessness/Hopelessness (HH), Anxious Preoccupation (AP), Fighting Spirit (FS), Avoidance (AV) and Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
74
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 27 publications
12
74
2
2
Order By: Relevance
“…As was expected, this coping strategy has positive relation with HRQoL. This finding is consistent with those of Anagnostopoulos et al (23) and Rottmann et al (24). Patients with high fighting spirit see cancer diagnosis as a challenge and view the future optimistically, and believe that it is possible to control the disease (7).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…As was expected, this coping strategy has positive relation with HRQoL. This finding is consistent with those of Anagnostopoulos et al (23) and Rottmann et al (24). Patients with high fighting spirit see cancer diagnosis as a challenge and view the future optimistically, and believe that it is possible to control the disease (7).…”
supporting
confidence: 83%
“…There is no significant correlation between fighting spirit and the QoL in other studies. Because of the relation between fatalism and QOL, some studies showed that it was a negative relation (20,21), while others showed a positive relation (22,23) or no significant correlation (24).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, however, avoidance becomes a detrimental strategy that distracts the patients from the seriousness of the problem. 63,64 The patients who use a fatalistic coping style feel that the diagnosis represents a relatively minor threat and that there is no control that can be exerted over the situation: the consequences of lack of control can and should be accepted with equanimity. This attitude, experienced sometimes in the course of the disease, may help patients to adapt, in a stoic sense, to cancerrelated life changes (''I've had a good life, what's left is a bonus'').…”
Section: Discussionmentioning
confidence: 98%
“…The Mini-MAC is also a well-known, validated tool [26][27][28], although its factor structure has been debated; several replication studies resulted in somewhat different structures [28,32,46], although others could replicate the original five-factor structure [27,47]. The difference in findings might be due, e.g., to cultural differences or the lack of comparability of the samples.…”
Section: Discussionmentioning
confidence: 99%